Rezension von: Packull, Werner O., "A Hutterite book of medieval origin" revisited - Wunder, Gerd (Württembergisch Franken, 1983)
Werner O. Packull: »A Hutterite Book of medieval origin« Revisted. In: The Mennonite Quarterly Review 56, April 1982, Nr. 2, S. 147-168.